2013
DOI: 10.3109/13880209.2013.764537
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying the tetrandrine-mediated reversal of the fluconazole resistance ofCandida albicans

Abstract: Context: Our previous study demonstrated that tetrandrine (TET) could reverse the resistance of Candida albicans to fluconazole. Objective: The aim of this study was to investigate the molecular mechanism underlying this action. Materials and methods: Real-time reverse transcription polymerase chain reaction (real-time RT-PCR) was performed to compare the expression levels of the drug resistance genes CDR1, CDR2, MDR1, FLU1 and ERG11 in fluconazole-sensitive CA-3 and resistant CA-16 cells that were either trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Mitochondrial complex V activity was measured by an assay kit according to the manufacturer’s protocol. For determinations of intracellular ATP concentrations, an aliquot of 1 × 10 6 cells from each strain was mixed with the same volume of BacTiter-GloTM reagent (Promega Corporation, Madison, WI, USA) and incubated for 5 min at room temperature as described previously ( Zhang et al, 2013 ). ROS measurement was performed by using a oxidation-sensitive fluorescent dye DCFDA ( Guo et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Mitochondrial complex V activity was measured by an assay kit according to the manufacturer’s protocol. For determinations of intracellular ATP concentrations, an aliquot of 1 × 10 6 cells from each strain was mixed with the same volume of BacTiter-GloTM reagent (Promega Corporation, Madison, WI, USA) and incubated for 5 min at room temperature as described previously ( Zhang et al, 2013 ). ROS measurement was performed by using a oxidation-sensitive fluorescent dye DCFDA ( Guo et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Several chemicals from traditional herbs, such as tetrandrine (Zhang et al 2013) and allicin (Khodavandi et al 2011), have been recognised as alternatives to enhance the antifungal activity of FLC. Flavonoids are a group of chemicals, and have also been reported to have broad-spectrum antibacterial and antifungal activities (Friedman 2007;Orhan et al 2010;Peralta et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study indicated that TET could inhibit the expression of MDR1, FLU1, CDR1, CDR2 and reduce drug efflux and increase the accumulation of intracellular azoles, thereby enhancing the sensitivity of C. albicans to FLC (Zhang et al . , 2013a). Zhang et al .…”
Section: The Antifungal Activity Of Traditional Chinese Medicinementioning
confidence: 99%
“…At present, research on the synergistic antifungal mechanism between TET and azoles has also been reported. A recent study indicated that TET could inhibit the expression of MDR1, FLU1, CDR1, CDR2 and reduce drug efflux and increase the accumulation of intracellular azoles, thereby enhancing the sensitivity of C. albicans to FLC (Zhang et al 2009(Zhang et al , 2013a. Zhang et al (2013b) also found that the synergistic mechanism of FLC and TET against C. albicans was related to inhibition of the drug efflux system by proteomic analysis.…”
Section: Tetrandrinementioning
confidence: 99%